(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
School education has suffered significant impacts due to the health pandemic caused by covid-19, either by the closure of educational institutions and suspension of classroom activities or the challenging scenario that emerges for the use of technology as a resource for pedagogical mediation. This experience report aims to describe the experience of live streaming on YouTube as an alternative for maintaining links between the Graduate Program in Education (PPGED) the State University of Southwest Bahia and the academic community during the period of suspension of classroom activities in the institution. In this narrative we describe the details of its planning and execution and situate the PPGED Lives Project in academic literature as an Scientific Online Event. The scope of the project suggests, a priori, that the majority of the audience is formed by teachers of basic education, a profile that characterizes the current and demanding public of PPGED, in addition to the academic community as a whole, showing the interest of this audience around the topics discussed in the broadcasts.